Donor Preconditioning After the Onset of Brain Death With Dopamine Derivate n‐Octanoyl Dopamine Improves Early Posttransplant Graft Function in the Rat. Issue 7 (28th February 2017) - Li, S.; Korkmaz‐Icöz, S.; Radovits, T.; Ruppert, M.; Spindler, R.; Loganathan, S.; Hegedűs, P.; Brlecic, P.; Theisinger, B.; Theisinger, S.; Höger, S.; Brune, M.; et al.
Abstract : Heart transplantation is the therapy of choice for end‐stage heart failure. However, hemodynamic instability, which has been demonstrated in brain‐dead donors (BDD), could also affect the posttransplant graft function. We tested the hypothesis that treatment of the BDD with the dopamine derivate n ‐octanoyl‐dopamine (NOD) improves donor cardiac and graft function after transplantation. Donor rats were given a continuous intravenous infusion of either NOD (0.882 mg/kg/h, BDD+NOD, n = 6) or a physiological saline vehicle (BDD, n = 9) for 5 h after the induction of brain death by inflation of a subdural balloon catheter. Controls were sham‐operated (n = 9). In BDD, decreased left‐ventricular contractility (ejection fraction; maximum rate of rise of left‐ventricular pressure; preload recruitable stroke work), relaxation (maximum rate of fall of left‐ventricular pressure; Tau), and increased end‐diastolic stiffness were significantly improved after the NOD treatment. Following the transplantation, the NOD‐treatment of BDD improved impaired systolic function and ventricular relaxation. Additionally, after transplantation increased interleukin‐6, tumor necrosis factor TNF‐α, NF‐kappaB‐p65, and nuclear factor (NF)‐kappaB‐p105 gene expression, and increased caspase‐3, TNF‐α and NF‐kappaB protein expression could be significantly downregulated by the NOD treatment compared to BDD. BDD postconditioning with NOD through downregulation of the pro‐apoptotic factor caspase‐3, pro‐inflammatory cytokines, and NF‐kappaB may protect the heart against the myocardial injuries associated with brain death and ischemia/reperfusion. Abstract : Postconditioning donors after the onset of brain death with dopamine derivate n ‐octanoyl dopamine improves posttransplant graft function in a rat model, in part via downregulation of the pro‐apoptotic factor caspase‐3, pro‐inflammatory cytokines tumor necrosis factor‐α and interleukin‐6, and nuclear factor kappaB.